A multifunctional platinum(iv) and cyanine dye-based polyprodrug for trimodal imaging-guided chemo–phototherapy. Issue 7 (26th January 2022) - Li, Shuying; Wu, Yanjuan; Liu, Siyuan; Wu, Ting; Liu, Guozheng; Li, Tianduo; Chen, Zhaowei
Abstract : This study reports an innovative polyprodrug, PCPP NPs, which could be used for near-infrared (NIR) fluorescence imaging, photothermal imaging, and Pt-based CT imaging guided chemo–phototherapy. Abstract : Imaging-guided chemo–phototherapy based on a single nanoplatform has a great significance to improve the efficiency of cancer therapy and diagnosis. However, high drug content, no burst release and real-time tracking of nanodrugs are the three main challenges for this kind of multifunctional nanotheranostics. In this work, we developed an innovative theranostic nanoplatform based on a Pt(iv ) prodrug and a near-infrared (NIR) photosensitizer. A Pt(iv ) prodrug and a cyanine dye (HOCyOH, Cy) were copolymerized and incorporated into the main chain of a polyprodrug (PCPP), which self-assembled into nanoparticles (NPs) with ∼27.61% Cy loading and ∼9.37% Pt loading, respectively. PCPP NPs enabled reduction-triggered backbone cleavage of polyprodrugs and bioactive Pt(ii ) release; Cy could be activated under 808 nm laser irradiation to produce local hyperthermia and reactive oxygen species (ROS) for phototherapy. Moreover, PCPP NPs with extremely high Cy and Pt heavy metal contents in the backbone of the polyprodrug could directly track the nanodrugs themselves via near-infrared fluorescence (NIRF) imaging, photothermal imaging, and computed tomography (CT) imaging in vitro and in vivo . As revealed by trimodal imaging, PCPP NPs were found to exhibit excellent tumor accumulation and antitumor efficiency after intravenous injection into H22-tumor-bearing mice. The dual-drug backboned polyprodrug nanoplatform exhibited great potential for bioimaging and combined chemo–phototherapy.